EFFICACY AND TOLERABILITY OF LAMITOR (LAMOTRIGINE) IN THE TREATMENT OF IDIOPATHIC FOCAL AND GENERALIZED EPILEPSY IN MONOTHERAPY AND IN POLYTHERAPY IN CHILDREN AND ADOLESCENTS - K. Yu. Mukhin; O. A. Pylaeva; M. B. Mironov (Русский журнал детской неврологии)
Results of research of efficacy and tolerability of lamitor (lamotrigine) in the treatment of idiopathic focal and generalized forms of epilepsy as monotherapy or in polytherapy in children and adolescents are presented. 25 patients were included in our research, aged from 2 till 18 years, with idiopathic focal (n=10) and generalized (n=15) epilepsy, which received lamitor in monotherapy (5 patients) or in polytherapy (20 patients). As a whole, remission was reached at 18 of 25 patients (72%), significant improvement – at 5 of 25 (20%), the effect was absent – 1 patient (4%), deterioration was noted only in 1 case (4%). Efficiency of lamitor in dependence on epilepsy form was considered. Good tolerability of lamitor is noted. Thus, our research demonstrated high efficiency and good tolerability of lamitor as an additional antiepileptic drug and in monotherapy in the treatment of idiopathic epilepsies in children and adolescents.